2020
DOI: 10.1038/s41598-020-59028-w
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin Domain Receptors, DDR1b and DDR2, Promote Tumour Growth within Collagen but DDR1b Suppresses Experimental Lung Metastasis in HT1080 Xenografts

Abstract: the Discoidin Domain Receptors (DDRs) constitute a unique set of receptor tyrosine kinases that signal in response to collagen. Using an inducible expression system in human HT1080 fibrosarcoma cells, we investigated the role of DDR1b and DDR2 on primary tumour growth and experimental lung metastases. Neither DDR1b nor DDR2 expression altered tumour growth at the primary site. However, implantation of DDR1b-or DDR2-expressing HT1080 cells with collagen I significantly accelerated tumour growth rate, an effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 156 publications
(247 reference statements)
0
22
0
Order By: Relevance
“…Cluster A was enriched in regulatory pathways associated with cell adhesion, correlating with the expression of DDR1, HOXA7, MMP2, THBS1, TNFRSF14, and TGFB2. (Wasinski et al, 2020;Xu et al, 2005) Cluster A was also enriched in pathways associated with cellular locomotion, corroborated by the expression of SERPINE1, PDGFA, ITGAV, and ITGB1BP1. (Heldin, 2013;Morandi et al, 2016) Both sets of upregulated genes were observed in CD44 high /EpCAM high lung-derived cells, but not MFP-derived or CD44 low /EpCAM high lung-derived cells.…”
Section: Cancer Cell Lines Exhibit Distinct Gene Expression Changes Rmentioning
confidence: 88%
“…Cluster A was enriched in regulatory pathways associated with cell adhesion, correlating with the expression of DDR1, HOXA7, MMP2, THBS1, TNFRSF14, and TGFB2. (Wasinski et al, 2020;Xu et al, 2005) Cluster A was also enriched in pathways associated with cellular locomotion, corroborated by the expression of SERPINE1, PDGFA, ITGAV, and ITGB1BP1. (Heldin, 2013;Morandi et al, 2016) Both sets of upregulated genes were observed in CD44 high /EpCAM high lung-derived cells, but not MFP-derived or CD44 low /EpCAM high lung-derived cells.…”
Section: Cancer Cell Lines Exhibit Distinct Gene Expression Changes Rmentioning
confidence: 88%
“…As a tumor-suppressive pathway, inactivation of Hippo signaling has been extensively reported to be involved in the progression and metastasis of numerous types of cancer (41,42), including fibrosarcoma (43)(44)(45). On the one hand, core components of the Hippo pathway MST1/2 and LATS1/2 were downregulated, and this downregulation was involved in the inactivation of Hippo signaling (46,47); on the other hand, upregulation of the Hippo pathway transcription coactivators YAP and TAZ further exacerbated inactivation of the Hippo signaling, promoting the development and progression of cancers (48).…”
Section: Discussionmentioning
confidence: 99%
“…While suppression of DDR1 has also been observed to reduce the invasive properties of other cancer cell lines such as melanoma, colon and hepatoma cells [44]. Interestingly, DDR1b and DDR2, promoted tumor growth in the presence of collagen while DDR1b suppressed the lung metastasis of HT1080 fibrosarcoma cells in a xenograft model [45]. Elucidating the interactions between TP53 and DDR1 and drug sensitivity could further our understanding of how the invasive properties of various cancer types is influenced by the presence of different types/classes of adult vs old collagen present in the extracellular matrix.…”
Section: Agingmentioning
confidence: 98%